2020
DOI: 10.1007/s40519-019-00842-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative meta-analysis of the prevalence of exercise addiction in adults with and without indicated eating disorders

Abstract: Background: Exercise addiction is associated with multiple adverse outcomes and can be classified as co-occurring with an eating disorder, or a primary condition with no indication of eating disorders. We conducted a meta-analysis exploring the prevalence of exercise addiction in adults with and without indicated eating disorders.Methods: A systematic review of major databases and grey literature was undertaken from inception to 30/04/2019. Studies reporting prevalence of exercise addiction with and without in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 61 publications
5
75
1
Order By: Relevance
“…As hypothesized, the strength of associations of the two variables that could be interpreted as "sudden or progressively intolerable life-stress" (eating disorder status and BDD status) in the Interactional Model of EA were among the strongest. This concurs with several studies that have shown that eating disordered subjects suffer from higher EA (Fietz et al, 2014;Trott et al, 2020b), and several studies that show that negative self-body image is positively correlated with exercise addiction (Klein et al, 2004;Ertl et al, 2018). Moreover, this provides initial evidence that these two conditions could be listed in the Interactional Model as possible intolerable life-events.…”
Section: Total Samplesupporting
confidence: 90%
See 2 more Smart Citations
“…As hypothesized, the strength of associations of the two variables that could be interpreted as "sudden or progressively intolerable life-stress" (eating disorder status and BDD status) in the Interactional Model of EA were among the strongest. This concurs with several studies that have shown that eating disordered subjects suffer from higher EA (Fietz et al, 2014;Trott et al, 2020b), and several studies that show that negative self-body image is positively correlated with exercise addiction (Klein et al, 2004;Ertl et al, 2018). Moreover, this provides initial evidence that these two conditions could be listed in the Interactional Model as possible intolerable life-events.…”
Section: Total Samplesupporting
confidence: 90%
“…Prevalence rates differed largely according to eating disorder status, with participants with indicated eating disorders yielding more than double the prevalence rates than those with no indicated eating disorders. These results are broadly in agreement with a recent meta-analysis that showed subjects with indicated eating disorders are over 3.5 times more likely to also have exercise addiction (Trott et al, 2020b). The overall exercise addiction prevalence rate is higher than in several reviews that have estimated prevalence between 3 and 14% (Di Lodovico et al, 2019;Marques et al, 2019).…”
Section: Exercise Addiction Prevalencesupporting
confidence: 90%
See 1 more Smart Citation
“…Different studies have suggested that higher levels of fitness might have a protective effect on the risk of FEDs in adolescents [18] and young adults [16]. Conversely, it should not be neglected that high levels of physical activity have been associated with FEDs in such a way that the risk of eating behavior disorders, both in men and women, is higher in athletes than in nonathletes and those considered with an exercise addiction [19,20]. Moreover, higher levels of physical activity could not only accelerate weight loss but also elicit a more severe FED psychopathology [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, there is no consensus on what constitutes problematic exercise in the context of eating disorders (Noetel et al, 2017). Indeed, an array of terminology has been used to describe the unhealthy relationship with exercise often observed in people with eating disorders, such as compulsive exercise (Bratland-Sanda et al, 2019;Dittmer et al, 2018;Lichtenstein et al, 2017), exercise addiction (Adams & Kirkby, 2002;Gri ths et al, 2005;Trott et al, 2020), exercise dependence (Blaydon & Lindner, 2002; Hausenblas & Downs, 2002), and obligatory exercise (Steffen & Brehm, 1999). A recent Delphi study indicated that 60% of international experts in the treatment of eating disorders preferred the term compulsive exercise, although it must be noted that 60% agreement did not meet their threshold for consensus (≥ 85% agreement) or near consensus (≥ 75% agreement; Noetel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%